Responsivity enhancement techniques for CMOS source‐driven terahertz detectors. Issue 6 (28th March 2022) - Wu, Hao; Fu, Haipeng; Meng, Fanyi; Ma, Kaixue
Abstract: The size and asymmetry effects of MOSFET detectors operating in a source‐driven configuration on responsivity are discussed in this paper. Seven MOSFET detectors with different sizes and structures are fabricated in a standard 55 nm CMOS technology. At 2.58 THz, the measurement results show that for the symmetric device, the minimum size MOSFET can achieve a higher responsivity, and for the asymmetric device, when the ratio of the source channel width to the drain channel width reaches 4:1 or higher, the asymmetric detector can achieve a higher responsivity than the detector based on the minimum size device available in the process. The best responsivity of the 2.03 kV/W is achieved by the asymmetry structure MOSFET detector with the ratio of the source channel width to the drain channel width reaching 4:1.